Characterization of a novel anti-lipopolysaccharide factor isoform (SpALF5) in mud crab, Scylla paramamosain. Issue 2 (April 2015) - Sun, Wanwei; Wan, Weisong; Zhu, Shuo; Wang, Shasha; Wang, Shuqi; Wen, Xiaobo; Zheng, Huaiping; Zhang, Yueling; Li, Shengkang
Highlights A novel isoform of ALFs (SpALF5) was isolated from the mud crabs. Be of characteristics of ALFs and highly induced upon immune challenges. A varying degree of binding activity to bacteria and a strong antimicrobial activity against G− bacteria.